KOMUNIKASI MILITER PADA REMAJA DALAM MENGAMBIL KEPUTUSAN MENJADI PRAJURIT TNI-AD DI KOREM 062 TARUMANAGARA GARUT - Devi Devi Prayoga; Achmad Wildan Kurniawan; Iis Zilfah Adnan; Zikri Fachrul Nurhadi (Lingkar Studi Komunikasi (LISKI), 2018)
This research is motivated by the number of teenagers who register themselves as an Army soldier is not denied that they have their own goals. Every year registration of TNI-AD especially in Garut City continues to increase. This is a new phenomenon where rarely had anyone wanted to be a soldier and devote himself to the state. The age limit of registration to become a soldier is 18-22 years old for high school graduates or equivalent. Entering the military world must have a strong mental and physical, especially must be good at communicating with subordinates and with superiors to avoid a miss communication at the time of duty. The purpose of this study is to find and explain about the motives, experiences, and meaning of adolescents as soldiers of the Army. This research use desciptive qualitative approach. Data collection techniques through in-depth interviews, participant observation, and literature study. The informants in the study as many as 8 people. The results showed that the motive for being a TNI-AD par excellence is the aspiration and economy, while the motive is due to the sense of nationalism, family and the environment. The existing experience of living in military environments, following organizations in schools, the influence of online action games, the existence of family education since childhood. Keywords : Communication, Military, Youth, Soldiers, Army